Associations Between TikTok Use and Mental Health Among Young Adults: A Systematic Review - Shuang Li; Julia Wirza Binti Mohd Zawawi; Nur Atirah Kamaruzaman (Youth, 2026)
TikTok is the fifth-most-popular social media platform worldwide and is particularly popular among young adults. In recent years, research on the association between TikTok use and mental health among young adults has increased substantially. Following the PRISMA guidelines, this systematic review examined empirical studies investigating this association. We conducted a comprehensive literature search across four electronic databases: PubMed, Web of Science, Scopus, and CNKI. We included and synthesized 11 eligible studies using narrative synthesis. The findings indicated that TikTok use was associated with both potential risks and benefits for the mental health of young adults. These psychological outcomes varied according to patterns of TikTok use and the content encountered on the platform. Individual psychological characteristics, sex, age, and algorithm awareness were also identified as potential factors that may shape this association. The existing literature was limited by the predominance of cross-sectional study designs, which precluded causal inference. Future research should prioritize longitudinal studies and randomized controlled trials to inform the development and evaluation of interventions to support healthier, more responsible for TikTok use among young adults.